Cross-linking and de-cross-linking of triarylimidazole-based polymer. (2nd September 2016) - Peng, Ya; Yu, Haiwen; Chen, Hongbiao; Huang, Zhichao; Li, Huaming
Abstract: The reversible addition-fragmentation chain transfer (RAFT) polymerization of 1-(4-(4, 5-diphenyl-1H-imidazol-2-yl)phenyl)-4-vinyl-1H-1, 2, 3-triazole (DVT) was carried out in N, N -dimethylformamide at 70 °C using 2-(ethylthiocarbonothioylthio)-2-methylpropanoic acid as the RAFT agent and 2, 2′-azobisisobutyronitrile as the initiator to give well-defined poly(DVT) (1 ). The cross-linking reaction of the obtained (1 ) was proceeded with K3 [Fe(CN)6 ] and KOH, yielding the intramolecular (2 ) and intermolecular cross-linked poly(DVT) (3 ) by tuning the polymer concentrations. The resulting cross-linked poly(DVT) (2 ) and (3 ) were de-cross-linked by visible light irradiation in the presence of ethanethiol, giving ethylthio-capped, de-cross-linked poly(DVT) (4 ) in good yield. Graphical abstract: The cross-linking reaction of the triarylimidazole-containing polymer (poly(DVT)) (1 )was proceeded with K3 [Fe(CN)6 ] and KOH, yielding the intramolecular (2 ) and intermolecular cross-linked poly(DVT) (3 ) by tuning the polymer concentration. The resulting cross-linked poly(DVT) (2 ) and (3 ) were de-cross-linked by visible light irradiation in the presence of ethanethiol, giving ethylthio-capped, de-cross-linked poly(DVT) (4 ). Highlights: Triarylimidazole-containing poly(DVT) was synthesized by RAFT polymerization. Intramolecular cross-linking of poly(DVT) was proceeded with C IM below 50 μM. Intermolecular cross-linking of poly(DVT) was proceeded with C IM above 500 μM. Cross-linked poly(DVT) can be de-cross-linked by visible light irradiation.